ANALISIS TREND PENELITIAN PENGEMBANGAN PADA PEMBELAJARAN FISIKA DI INDONESIA - Dimas Permadi; Wayan Suana; Anggreini Anggreini; Rindi Novitri Antika (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2024)
The purpose of this research is to map the trends in physics education development research in Indonesia. The research method used in this study is qualitative descriptive research. The data collection technique used in this research is documentation. The data analysis technique used is qualitative descriptive in the form of data reduction, data display, and conclusion drawing. The results of the research show that there are 689 article titles on development research in the field of Physics. The current trend in development research is the development of electronic-based media and assessment instruments, using both PCs and Android applications. The most widely used development research models are 4D, ADDIE, and Brog & Gall. Development research has also focused on high-level thinking skills, as evidenced by the appearance of keywords related to critical thinking in physics development research. Future development research can focus on the use of technology, such as Augmented Reality, Virtual Reality, Android applications, and the use of AI.